2009
DOI: 10.1177/0363546508330974
|View full text |Cite
|
Sign up to set email alerts
|

Use of Autologous Platelet-rich Plasma to Treat Muscle Strain Injuries

Abstract: Background Muscle strains are one of the most common injuries treated by physicians. Standard conservative therapy for acute muscle strains usually involves short-term rest, ice, and non-steroidal anti-inflammatory medications, but there is no clear consensus on how to accelerate recovery. Hypothesis Local delivery of platelet-rich plasma (PRP) to injured muscles hastens recovery of function. Study Design Controlled laboratory study. We used an established animal model of injury to test the effects of auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
214
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 271 publications
(225 citation statements)
references
References 39 publications
4
214
0
7
Order By: Relevance
“…Standard nonoperative therapy for acute muscle injuries usually involves rest, ice, compression, and elevation (RICE). Although experimental therapies such as platelet-rich plasma [15], suramin [6], and other such agents [14,30,42] are being tested, there is no clear consensus on nonoperative treatment of muscle injuries beyond the principle of short-term rest and ice.…”
Section: Discussionmentioning
confidence: 99%
“…Standard nonoperative therapy for acute muscle injuries usually involves rest, ice, compression, and elevation (RICE). Although experimental therapies such as platelet-rich plasma [15], suramin [6], and other such agents [14,30,42] are being tested, there is no clear consensus on nonoperative treatment of muscle injuries beyond the principle of short-term rest and ice.…”
Section: Discussionmentioning
confidence: 99%
“…Delos et al found no difference in muscle strength at any time point and no difference in the number centronucleated fibers or inflammatory cells compared to control rodents injected with saline [42]. Hammond et al found no difference in strength for single muscle contraction injuries treated with PRP [43]. However, they did show increased muscle regeneration, improved contractile function of multiple muscle contraction injured muscles, and decreased recovery time from 21 to 14 days compared to controls.…”
Section: Treatments To Enhance Return To Sports After Muscle Injurymentioning
confidence: 99%
“…Hammond et al studied the effects of PRP on the recovery of contractile function in Sprague-Dawley rats injured by a single large strain or multiple small strain lengthening contractions of the tibialis anterior muscles (TA) [23]. The high repetition model demonstrated significant improvements in measures of satellite cell activation and quantification of myogenesis in PRP vs. control groups that peaked at 2 weeks.…”
Section: Potential Adverse Effectsmentioning
confidence: 99%